Marstrand's Approximate Independence of Sets and Strong Differentiation of the Integral - Cabral, Raquel (Mathematica Scandinavica, 2016)
A constructive proof is given for the existence of a function belonging to the product Hardy space $H^1(\mathsf{R} × \mathsf{R})$ and the Orlicz space $L(\log L)^{ε}(\mathsf{R}^{2})$ for all $0